A Correlation Between The Role of Health Workers and Treatment Costs With Patient Satisfaction at The Dental Polyclnic of Lesung Batu Health Center, Empat Lawang Regency - Koko Rolanda; Darmawansyah Darmawansyah; Fikitri Marya Sari (Student Scientific Journal, 2026)
Background: Dental and oral health issues are significant public health concerns worldwide. Many factors influence the utilization of health services, including the role of health workers, facilities and infrastructure, treatment costs, and the distance to the community health center, all of which affect patient satisfaction. Objective: This study aims to determine the relationship between the role of health workers and treatment costs with patient satisfaction at the Dental Polyclinic of Lesung Batu Health Center, Empat Lawang Regency. Metods: The method used is an analytical survey with a cross-sectional design. Data were collected as primary data by distributing questionnaires to 35 patients receiving treatment at the Dental Polyclinic, using total sampling technique. Data analysis was performed using the Chi-Square test. Research results: Univariate analysis results indicate an average health worker role score of 3.40, an average treatment cost of Rp. 41,714, and an average patient satisfaction score of 92.94. Bivariate analysis shows a significant relationship between the role of health workers and patient satisfaction (p=0.001) and between treatment costs and patient satisfaction (p=0.002). Conclusion : The researchers recommend that the health center conduct outreach to schools and POSYANDU (integrated health posts) to educate children and mothers with toddlers on proper dental and oral health maintenance.